Anxiety in elite young gymnasts: Part II : Sources of stress - Duda, J. L.; Gano-Overway, L. (Technique, 1996)
Part II of this series (Technique, March 1996) revealed that young, talented gymnasts define stress as a negative response manifested in their bodies, thoughts, feelings as well as in terms of the situation in which they find themselves. These personal definitions of anxiety clearly indicated that stress diminishes the quality of their gymnastics experience. As the stress response is a result of a perceptual process, we need to know what gymnasts perceive to be causing them to feel anxious if we hope to decrease the frequency and intensity of stress in gymnastics (and foster the occurrence of relaxation states). Sport psychology research on the antecedents of stress have revealed the following sources: 1.low perceived mental and physical readiness 2.high levels of fatigue 3.others' high expectations 4.fear of failure and/or making a mistake 5.the perceived importance of the competition 6.an overemphasis on outcome 7.fear of negative evaluation 8.forced participation in the activity at hand